PENERAPAN METODE AGE REPLACEMENT PADA USULAN JADWAL PREVENTIVE MAINTENANCE MESIN DUMP TRUCK DI PT. BSE BAYUNG LENCIR - Dio, Alfhand Dian; MZ, hermanto; tamalika, tolu (Nusantara of Engineering (NOE), 2023)
The mobility of the course of the production process of a mining company will increase if the means of transportation used are better. PT BSE Bayung Lencir as a provider of Dump truck transportation equipment has three fleets, including the Dump trucks of Renault, Scania and Mercy. In the Dump truck fleet there are many that are damaged so that they cannot operate and cause losses, both in terms of repair costs and due to the non-operation of the fleet. The Dump truck brand that experienced the most damage was the Mercy brand with 34 cases. Therefore, it is necessary to plan a preventive maintenance schedule for Dump truck engines so that PT BSE Bayung Lencir's consumer needs can be met and the costs incurred can be kept to a minimum. The stages in the research began with collecting data, analyzing data using the Age Replacement Method. after treatment with the AgeReplacement method, the right treatment time to do is every 24 days at a cost of Rp. 16,726,146, - the cost before determining the treatment time is Rp. 24,500,000, - thus the profit earned is Rp. 7,773,854, - So the company can make savings of 31%.